Thibbun Nabawi Herbs for Breastfeeding Mothers - Arum Meiranny; Isna Hudaya; Afita Dini Sukmana (Alma Ata University Press, 2020)
The effect of herbal consumption on breastfeeding mothers frequently associated with the breast milk production and the restoration of mothers’ stamina after child birth. Herbs have a composition that help the recovery process of post partum mothers and increase the breast milk production. There fore, the use of prophetic medicine can be the solution. To find out the practice of Thibbun Nabawi Herbs on breastfeeding mothers. The search of journal article electronically by using a data base in Google Scholar. Keywords that are being used are “Thibbun Nabawi/Prophetic Medicine”, “Herbal/Herbs” and “Breastfeeding”, until 3 article was obtained to be reviewed. The use of some Thibbun Nabawi herbs like dates, honey and black cumin/habbatussauda’ can effect the breast milk production on breastfeeding mothers. The use of thibbun nabawi herbs for post partum mothers is very recommended because it can increase the production of breast milk and giving happiness to the post partum mothers and able to reduce the risk of baby blues syndrome. Thibbun Nabawi herbs can effect the production of breast milk on post partum mothers.